2018
DOI: 10.1111/1467-9566.12764
|View full text |Cite
|
Sign up to set email alerts
|

Agency, activation and compatriots: the influence of social networks on health‐seeking behaviours among Sri Lankan migrants and Anglo‐Australians with depression

Abstract: The nexus between social networks and illness behaviours is important in uptake of health care, however scant research has explored this relationship in South Asian migrants living with mental illness. We explored the interplay between culture, social networks and health seeking in Sri Lankan migrants and Anglo-Australians living with depression. Forty-eight in-depth interviews were conducted and data were analysed through the theoretical prism of the network episode model. Results showed that social networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
(95 reference statements)
0
9
0
Order By: Relevance
“…Strong interpersonal dynamics in these relationships are thought to signi cantly affect an individual's physical and mental health and health decision-making (15)(16)(17)(18)(19)(20). Studies have shown that social in uence from interpersonal relationships signi cantly affects health behaviors, including health-seeking behavior, breastfeeding practices, and uptake of family planning methods (21)(22)(23)(24)(25)(26). This also applies to immunization, as literature has highlighted that people who believe that individuals within their social network want them to be vaccinated are more likely to accept vaccines (27)(28)(29)(30).…”
Section: Interpersonal-level Factorsmentioning
confidence: 99%
“…Strong interpersonal dynamics in these relationships are thought to signi cantly affect an individual's physical and mental health and health decision-making (15)(16)(17)(18)(19)(20). Studies have shown that social in uence from interpersonal relationships signi cantly affects health behaviors, including health-seeking behavior, breastfeeding practices, and uptake of family planning methods (21)(22)(23)(24)(25)(26). This also applies to immunization, as literature has highlighted that people who believe that individuals within their social network want them to be vaccinated are more likely to accept vaccines (27)(28)(29)(30).…”
Section: Interpersonal-level Factorsmentioning
confidence: 99%
“…Therefore, initiatives that aim to promote gender equality in a traditional society need to consider how to avoid disempowering women by reducing the respect for their expertise. In terms of addressing the worldwide concern of antibiotics overuse (Gajdács and Albericio, 2019), scholars' recommendations to engage lay community health workers in formal health promotion initiatives has been proposed in several studies (Adams, 2020;Antoniades et al, 2018). This study's findings suggest that within collectivist societies and minority populations, hierarchical relations among women could be positively channelled to curb antibiotics use.…”
Section: Discussionmentioning
confidence: 88%
“….] the role of social networks is pivotal in uptake of formal care, and engaging with communities to improve responses of social networks to mental illnesses may provide a bottom-up avenue for improving uptake of mental health services in migrant communities" (Antoniades et al, 2018(Antoniades et al, , p. 1376.…”
Section: Physical Health (Transplantation Cancer Coronarymentioning
confidence: 99%